2021
DOI: 10.3390/ijerph18062886
|View full text |Cite
|
Sign up to set email alerts
|

Gender Specificity of Spousal Concordance in the Development of Chronic Disease among Middle-Aged and Older Chinese Couples: A Prospective Dyadic Analysis

Abstract: This study aimed to explore the gender specificity of spousal concordance in the development of chronic diseases among middle-aged and older Chinese couples. Data of 3420 couples were obtained from the China Health and Retirement Longitudinal Study (CHARLS). Multivariate logistic regression was used to analyze the incidence of chronic disease development over 4 years, conditional on the spousal baseline chronic disease status; and stepwise adjusting for the couples’ sociodemographic characteristics (i.e., age,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Our previous qualitative study on older Chinese couples with T2DM revealed that wives, regardless of their health status, were more actively involved in or fully responsible for taking care of their husband’s disease management, whereas husbands were less engaged in their wives’ care activities [ 36 ]. Older Chinese men highly relied on their partner for daily care, to the extent that these husbands whose spouses had a chronic disease had higher risk of becoming chronically ill over time [ 37 ]. Under this circumstance, our couple-based intervention is important as it fosters a sense of responsibility and a great willingness to collaborate as a partner to manage T2DM, particularly for husbands who otherwise are less aware of the needs of their wives.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous qualitative study on older Chinese couples with T2DM revealed that wives, regardless of their health status, were more actively involved in or fully responsible for taking care of their husband’s disease management, whereas husbands were less engaged in their wives’ care activities [ 36 ]. Older Chinese men highly relied on their partner for daily care, to the extent that these husbands whose spouses had a chronic disease had higher risk of becoming chronically ill over time [ 37 ]. Under this circumstance, our couple-based intervention is important as it fosters a sense of responsibility and a great willingness to collaborate as a partner to manage T2DM, particularly for husbands who otherwise are less aware of the needs of their wives.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding lifestyles and health management, husbands may be more dependent on their spouses. Women with obese spouses are more likely to have chronic diseases such as obesity, HTN, and DM 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the behaviors between spouses might influence each other, which suggests that interventions targeted at couples may be more effective than those targeted at individuals [ 9 ]. A few studies have demonstrated concordance of cardiovascular risk factors between Chinese couples [ 2 , 16 , 17 ]. However, two of these studies were with participants from cities in southern China [ 2 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cultural differences between northern and southern China may affect the concordance of couples’ lifestyles. Liao et al focused only on middle-aged and elderly couples and merely studied the concordance of chronic disease, not lifestyles [ 16 ]. Moreover, to the best of our knowledge, concordance of hyperuricemia between couples has not been reported.…”
Section: Introductionmentioning
confidence: 99%